Prevalenc of Acquired cyctic kidney disease and its relation with anemia in ESRD patients at Hemodialysis center - الحسامي محمد يحيى; حسين سعيد; فراس حسين (Latakia University Journal -Medical Sciences Series, 2024)
Background. Acquired renal cystic disease is an important complication of end-stage chronic kidney disease (ESRD) that is not widely studied and has a poorly defined clinical course. The development of AKI is often asymptomatic, and the most serious complications are retroperitoneal hemorrhage and renal cell carcinoma. The aim of this study was to investigate the prevalence of acquired CKD in these patients and its relationship with anemia, duration of hemodialysis therapy, and arterial hypertension. Methods: : The study included 150 patients who underwent kidney ultrasound with end-stage chronic kidney disease at the hemodialysis department at Tishreen University Hospital from 2022-2024 Results: The incidence of Acquired renal cystic disease was 21.3% during the first year of evaluation and increased to 36% a year later at re-evaluation. Arterial hypertension was the most common comorbidity in the study sample (72%), followed by diabetes mellitus (29.3%). The most common reason for the need for hemodialysis treatment was hypertension (66.7%), followed by diabetes mellitus (28.7%). The category of patients treated with hemodialysis less than 3 years old was the highest in the studied research sample with 60.7%. 50.7% of patients in the study sample had at least one cyst in at least one kidney. 59.3% of patients in the study sample had moderate anemia (7-10 g/dL). The age group older than 40 years was the highest percentage of the research sample, amounting to 73.3%. Conclusion: Acquired renal cystic disease is a common complication in patients with end-stage chronic kidney disease treated with hemodialysis.